2004
DOI: 10.1093/annonc/mdh355
|View full text |Cite
|
Sign up to set email alerts
|

Safety of sentinel node biopsy in pregnant patients with breast cancer

Abstract: According to our standard technique (12 MBq of 99mTc-HAS), LS and SLNB can be performed safely during pregnancy, since the very low prenatal doses from this diagnostic procedure, when properly performed, do not significantly increase the risk of prenatal death, malformation or mental impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
21

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(99 citation statements)
references
References 11 publications
1
77
0
21
Order By: Relevance
“…Using two nonpregnant patient exposures, Keleher and colleagues [52] in 2004 estimated the maximum absorbed dose to the fetus/embryo in pregnant women undergoing breast lymphoscintigraphy with 92.5MBq (2.5mCi) of 99m Tc-Sulfur Colloid as 4.3 mGy using the Medical Internal Radiation Dosimetry (MIRD) program. The same year, Gentilini and colleagues [53] measured activity using thermoluminescent dosimeters combined with static and whole-body scintigraphic imaging in 26 nonpregnant patients exposed to lymphoscintigraphy and overestimated the fetal absorbed dose as 61 mGy. In 2006, Pandit-Taskar and colleagues [54] retrospectively assessed the absorbed doses to various organs and a modeled fetus using standard internal absorbed dose assessment methodologies and phantom models in 1021 nonpregnant women undergoing sentinel node mapping and biopsy and estimated the absorbed fetal dose as 14 mGy.…”
Section: Management Of the Axillamentioning
confidence: 99%
“…Using two nonpregnant patient exposures, Keleher and colleagues [52] in 2004 estimated the maximum absorbed dose to the fetus/embryo in pregnant women undergoing breast lymphoscintigraphy with 92.5MBq (2.5mCi) of 99m Tc-Sulfur Colloid as 4.3 mGy using the Medical Internal Radiation Dosimetry (MIRD) program. The same year, Gentilini and colleagues [53] measured activity using thermoluminescent dosimeters combined with static and whole-body scintigraphic imaging in 26 nonpregnant patients exposed to lymphoscintigraphy and overestimated the fetal absorbed dose as 61 mGy. In 2006, Pandit-Taskar and colleagues [54] retrospectively assessed the absorbed doses to various organs and a modeled fetus using standard internal absorbed dose assessment methodologies and phantom models in 1021 nonpregnant women undergoing sentinel node mapping and biopsy and estimated the absorbed fetal dose as 14 mGy.…”
Section: Management Of the Axillamentioning
confidence: 99%
“…The surgical approach may be wide local excision along with exploration or dissection of local nodal groups. Sentinel lymph node biopsy was recently proposed to localize, recognize and remove metastatic axillary lymph nodes from ectopic breast cancer [7,8]. Whether ipsilateral breast irradiation offers an advantage is not exactly known.…”
Section: Discussionmentioning
confidence: 99%
“…The results of at least five studies examined safety of the procedure for fetus in pregnant patients affected with melanoma or breast cancer. Gentilini et al (Gentilini et al, 2004) have indirectly estimated the possible fetus exposure after application of radiopharmaceutical and its distribution in 26 premenopausal nonpregnant patients. They concluded that fetus exposure would be minimal and therefore the procedure could be safe for application in pregnant patients.…”
Section: Sentinel Nodementioning
confidence: 99%